(3efJgi GdEOQGc aj eOQc GdCadGcs - (3eLghds
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg Cf CYQVgG Ydi MceGA GdGeUGQ hYdeGA GdGbWGQ ai JVGYja JMQjQ cJGH eTJed Ydi RHOI GdeHShWGJ GdeDdaI s
(3BNQgG (B:s
(3hai GdGNQ GfNSa fUa ef LGfH GdTeGd hcGf YQVg HMSH GdJObjb ai GdESJNQGL s
(3HgG CTcGd hQShes
(3HgG GKGQ WeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs